Amyloid-like Hfq interaction with single-stranded DNA: involvement in recombination and replication in Escherichia coli. (7th September 2022) - Kubiak, Krzysztof; Wien, Frank; Yadav, Indresh; Jones, Nykola C.; Vrønning Hoffmann, Søren; Le Cam, Eric; Cossa, Antoine; Geinguenaud, Frederic; van der Maarel, Johan R. C.; Węgrzyn, Grzegorz; Arluison, Véronique
Abstract: Abstract: Interactions between proteins and single-stranded DNA (ssDNA) are crucial for many fundamental biological processes, including DNA replication and genetic recombination. Thus, understanding detailed mechanisms of these interactions is necessary to uncover regulatory rules occurring in all living cells. The RNA-binding Hfq is a pleiotropic bacterial regulator that mediates many aspects of nucleic acid metabolism. The protein notably mediates mRNA stability and translation efficiency by using stress-related small regulatory RNA as cofactors. In addition, Hfq helps to compact double-stranded DNA. In this paper, we focused on the action of Hfq on ssDNA. A combination of experimental methodologies, including spectroscopy and molecular imaging, has been used to probe the interactions of Hfq and its amyloid C-terminal region with ssDNA. Our analysis revealed that Hfq binds to ssDNA. Moreover, we demonstrate for the first time that Hfq drastically changes the structure and helical parameters of ssDNA, mainly due to its C-terminal amyloid-like domain. The formation of the nucleoprotein complexes between Hfq and ssDNA unveils important implications for DNA replication and recombination.